Analisis pemenuhan hak pendidikan anak didik di Lembaga Pemasyarakatan Khusus Anak - Annisa Saputri; Sawaludin Sawaludin; Bagdawansyah Alqadri (Journal of Education, Cultural and Politics, 2026)
This study aims to analyze the implementation of the fulfillment of the educational rights of Correctional Students at LPKA Class II Central Lombok, including driving and inhibiting factors, as well as the efforts undertaken by the in stitution. This study uses a qualitative approach with a case study type. Data were collected through observation, interviews, and documentation. The research results show that the fulfillment of the right to education is carried out through formal and non-formal education paths. Formal education is conducted through cooperation with SD-SMP Satu Atap 02 Batukliang and SMA Negeri 1 Batukliang Utara, while non-formal education is implemented through PKBM Andikpas with Paket A, Paket B, and Paket C programs as well as skills development. Encouraging factors include institutional policies and commitments, institutional support, and cooperation with external parties. Inhibiting factors include administrative obstacles, lack of family support, limited educational personnel, and children's characteristic conditions. The institution's efforts include coordination with schools and families, facilitating distance learning, and adjustments to education paths. The study concludes that the fulfillment of the right to education has been carried out, but there is still a need to strengthen resources and administration.